APPLICATION OF THE DOUBLE MATCH METHOD FOR DETERMINING THE CARRIER FREQUENCY OF HIDDEN INFORMATION TRANSMISSION SYSTEMS - PETRUSHAK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Among the technical means of detecting a leak of information on a radio channel, devices for measuring the frequency of a radio signal occupy an important place. So, for example, with the help of such frequency meters, it is possible to quickly determine the carrier frequency of hidden information transmission systems over a radio channel with a pseudo-random setting of the operating frequency. The problem of fast conversion of radio signal frequency for monitoring the radial velocity of a moving object. The object of the study was the process of converting frequency into a code based on the double match method. The goal of the work is to improve the double match method for creating a new signal-to-code frequency converter without fixing the conversion time interval. The double match method for converting the signal frequency into a code has been improved. The improved frequency conversion method, unlike the existing ones, consists in counting the number of complete phase cycles of the known and unknown signals during the time of double double match and asynchronous mode of hardware determination of the particle. The improved method has advantages in comparison with the method of an electro-counter frequency meter when determining the radial speed of objects and does not have a methodical error, which in an electro-counter frequency meter increases as the unknown frequency approaches the reference to 100%. However, the improved double match method compared to other versions has a hardware scheme for tracking the moments of double match and determining the fraction and does not require expensive and high-speed microprocessors to calculate the conversion results. Based on the phase-frequency interpretation and the derived conversion equation and the proposed frequency-to-code conversion scheme using the double match method, a functional scheme of the frequency converter was developed. This made it possible to implement a 8-bit frequency converter in code on Intel’s MAX V series CPLD. The double match method for converting the signal frequency into a code received further development, which, unlike the existing ones, consists in counting the number of complete phase cycles of the known and unknown signals during the time of double double match and the asynchronous mode of hardware determination of the fraction. The influence of the frequency of signals on the time of a single measurement was studied using the double match method, as a result of which it was found that with an increase in the difference between the reference and unknown frequency, the time of a single measurement decreases. The obtained research results can be used for the development of high-speed means of determining the frequency of the carrier, hidden systems of information transmission over the radio channel, with pseudo-random setting of the operating frequency.